2012
DOI: 10.4317/medoral.17323
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and serum interleukin 1 beta, interleukin 6 and tumor necrosis factor alpha in patients with leukoplakia and oral cancer

Abstract: Objectives: The aim of study was to compare salivary and serum concentrations of interleukin 1 beta (IL-1β), interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) in patients with oral leukoplakia, oral cancer and healthy controls. Study design: Eighty eight patients (28 with oral cancer, 29 leukoplakia, and 31 healthy controls) were included in this study. Cytokine concentrations were measured by commercial enzyme linked immunoassay. Results: Salivary IL-1β and IL-6 were significantly higher in oral ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 26 publications
12
128
1
6
Order By: Relevance
“…Similar observation was reported by Jablonska et al (1997) wherein they observed a relation between clinical staging and increase in serum TNF-α level in oral cavity cancer (Jablonska et al, 1997). TNF-α has also been shown to be a potential monitoring molecule for transformation of premalignant to malignant condition in oral cancer (Brailo et al, 2012;Juretic et al, 2013). Thus, the results of the present study also substantiate the observation of earlier reports wherein we observed a significant increase in TNF-α in premalignant disorder group but the increase was significantly lower than OSCC group.…”
Section: Discussionsupporting
confidence: 66%
“…Similar observation was reported by Jablonska et al (1997) wherein they observed a relation between clinical staging and increase in serum TNF-α level in oral cavity cancer (Jablonska et al, 1997). TNF-α has also been shown to be a potential monitoring molecule for transformation of premalignant to malignant condition in oral cancer (Brailo et al, 2012;Juretic et al, 2013). Thus, the results of the present study also substantiate the observation of earlier reports wherein we observed a significant increase in TNF-α in premalignant disorder group but the increase was significantly lower than OSCC group.…”
Section: Discussionsupporting
confidence: 66%
“…Use of salivary biomarkers as a diagnostic tool at the point of care has been tested for detection of numerous conditions and diseases, such as acute myocardial infarction, 7,14) oral cancer, [15][16][17][18] pancreatic cancer, 19) cardiovascular disease, [20][21][22] human immunodeficiency virus (HIV) status and periodontal disease .7,9,11,23) 4) Scientific merits and convenience for conducting research Salivary biomarkers offer scientific merits and convenience for conducting research, particularly studies on the physiological mechanisms of the stress response.…”
Section: ) Diagnostic Utilitymentioning
confidence: 99%
“…15,46) Inflammatory biomarkers have contributed to advancing our understanding of the role of inflammation in stress physiology. 12,30) The HPA axis and autonomic nervous system responses to stress manifest in lowering immune function as shown by numerous studies for the last three decades.…”
Section: ) Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pathways have been schematically identified as the connection between initiation of cancer and inflammation, as intrinsic pathway and extrinsic pathway. In the intrinsic pathway, internal genetic events which cause neoplasia, at the same time, would trigger the expression of inflammation-related programs and then guide the construction of an Factors Biological activity IL-1 Elevated level in patient with leukoplakia and oral cancer [71]; Inducing chemical carcigenesis of fibrosarcomas, in vivo [72]; host derived or exogenous IL-1 enhancing tumor invasiveness and metastasis, in vitro and in vivo [73] IL-6 Involved in tumor progression, such as in multiple myeloma, plasmacytomas, intestinal cancer, in vitro and in vivo, mainly through NF-κB and STAT3 [74]; Elevated IL-6 level be correlated with HCC, in vivo experiment and in clinical [75,76]; Elevated level in patient with leukoplakia and oral cancer [71] IL-23 Elevated in intestinal polyps and colorectal carcinoma [77] IFNEnhancing the antitumor activity of alveolar macrophages, in vitro [78] TNFElevated level in patient with leukoplakia and oral cancer [71] LXs Inhibiting the tumor growth of transplanted H22 in mice, in vitro and in vivo [79]; inhibiting hepatocyte growth factor-induced invasion of human hepatoma cells, in vitro [80] There is also close connection between inflammation and metastasis. A successful establishment of a metastatic lesion depends on both intrinsic properties of the tumor cells and factors derived from the tumor microenvironment that often contains secretory products of immune cells such as IL-1, IL-6, TNF and RANKL.…”
Section: Key Factors and Cells In Cancer-related Inflammationmentioning
confidence: 99%